C-PEPTIDE IS THE BETTER MARKER TO RULE OUT PREDIABETES IN CHRONIC PANCREATIC DISORDER PATIENTS - Rani Akuri, Sujatha; P, Ravi. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
C-peptide is considered as better marker for beta cell function in newly detected diabetes patients.Â Present study we are studying Serum C-Peptide levels of 30 chronic pancreatic patients and 20 healthy volunteers to rule out the prediabetes in chronic pancreatic disorder patients.Â From this study by analysing the result we found that the mean of fasting serum C-peptide levels in cases as 1.03 ng/mL with standard deviation of 0.38 is lower when compared with controls with mean value observed in control group is 3.55 with standard deviation of 1.12. The P value of fasting serum levels of C-peptide in cases and controls is 0.00. The mean of 2nd hr serum C-peptide levels in cases as 2.91 ng/mL with standard deviation of 0.86, the mean value observed in control group is 5.43 with standard deviation of 1.05 is higher in controls. The P value of 2nd hr serum levels of C-peptide in cases and controls is 0.00, hence there is a significant difference showing low levels in cases. Serum C-peptide levels are higher in controls compared to cases. This indicates that there is significant beta cell dysfunction in cases compared to controls. This leads to diabetic condition in chronic pancreatic disorder patients. Â Key words: C-Peptide, beta cell, Prediabetes, serum, chronic pancreatic disorder